Prevalence and clinical features of celiac disease in patients with autoimmune thyroiditis: cross-sectional study - Ventura, Aline; Ronsoni, Marcelo Fernando; Shiozawa, Maria Beatriz Cacese; Dantas-Corrêa, Esther Buzaglo; Canalli, Maria Heloisa Busi da Silva; Schiavon, Leonardo de Lucca; Narciso-Schiavon, Janaína Luz (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Celiac disease is an autoimmune disorder with an average prevalence of 1% in Europe and the United States. Because of strong European ancestry in southern Brazil, this study aimed to evaluate the seroprevalence of celiac disease among autoimmune thyroiditis patients. DESIGN AND SETTING: Cross-sectional study in a public university hospital. METHODS: This cross-sectional prevalence study included autoimmune thyroiditis patients who were tested for anti-endomysial and anti-transglutaminase antibodies between August 2010 and July 2011. RESULTS: Fifty-three patients with autoimmune thyroiditis were included; 92.5% were women, with mean age of 49.0 ± 13.5 years. Five patients (9.3%) were serologically positive for celiac disease: three of them (5.6%) were reactive for anti-endomysial antibodies and two (3.7%) for anti-transglutaminase. None of them exhibited anemia and one presented diarrhea. Endoscopy was performed on two patients: one with normal histology and the other with lymphocytic infiltrate and villous atrophy. CONCLUSION: The prevalence of celiac disease among patients with autoimmune thyroid disease was 9.3%; one patient complained of diarrhea and none presented anemia. Among at-risk populations, like autoimmune thyroiditis patients, the presence of diarrhea or anemia should not be used as a criterion for indicating celiac disease investigation. This must be done for all autoimmune thyroiditis patients because of its high prevalence.